EFFECTIVENESS OF PELVIC FLOOR MUSCLE EXERCISES ON QUALITY OF LIFE IN ELDERLY ELDERLY WITH URINARY INCONTINENCE: LITERATURE REVIEW - Ni Kadek Diahwinny Indrayani; Ni Putu Geg Mas Widya Candra Pinasthy; Made Juliani; Ni Wayan Dewi Tarini; Made Ririn Sri Wulandari (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Background:Urinary incontinence in the elderly has serious physical, psychological, and social impacts, and reduces quality of life. Pelvic Floor Muscle Exercise (PFME) is recommended as an effective non-pharmacological intervention, but its implementation is still limited. Objective: To evaluate the effectiveness of PFME on quality of life in elderly with urinary incontinence. Methods: A systematic literature review based on PRISMA guidelines of 15 primary articles published between 2014–2024, with inclusion criteria focusing on the elderly, PFME interventions, and quality of life measurements. Results: PFME consistently reduced the frequency of incontinence, increased voiding control, and improved physical and psychological quality of life. In elderly women, PFME reduced the frequency of incontinence by 74% (p > 0.05); in post-prostatectomy men, the combination of PFME with an oscillating rod increased the continence rate from 43% to 74% (p < 0.01). PFME was also effective in older adults with mild cognitive impairment, reducing daily episodes from 3.3 to 1.7 (p < 0.001), as well as increasing self-efficacy and decreasing depression scores (p < 0.01). Online approaches such as “teleGROUP” also showed positive long-term results (73% symptom reduction, p < 0.001). Conclusion: PFME has been shown to be an effective, safe, and adaptive intervention for the management of urinary incontinence in older adults, with a significant impact on quality of life. Educational support, technology, and an individualized approach can enhance its successful implementation.